Woodwork is Spice - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes how woodwork is a defining feature in a home's interior design. Suggests ways for painting old wood, staining new wood, and varnishing. Provides instructions for applying varnish and preparing wood for finishing treatment. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint